PENGARUH MASASE OLAHRAGA DAN PEREGANGAN EKSTREMITAS ATAS TERHADAP KELENTUKAN ATLET HOCKEY UNESA - , WINDRO; ANITA KUMAAT, NOORTJE (Jurnal Kesehatan Olahraga, 2019)
Sport Massage is not only needed for sportsmen but also needed for people who are not sportsmen for the sake of what is needed and restoring weak physical conditions with stimulating effects on bodily functions and carried out activities, besides Sports massage also affects flexibility. This study aims to determine the effect of sport massage manipulation and stretching on athletes flexibility Hockey Unesa, with a research sample of 12 active athletes in routine training at the UNESA UKM Hockey. This study uses a type of experimental research with a pre-post test design method. Instrument test for measurement of flexibility using a sit and reach tool. For data analysis the results of the study were processed by t test, with a significant level of 0.05. The results of the study can be seen from the average value of the pre-test and post-test results of UNESA Hockey athletes. The difference in the average value of 6.34 cm sports massage while the average value of stretching is 4,5 cm. It can be concluded that administration of sports massage and stretching of the upper extremities affect the flexibility, this effect is evidenced by an increase in flexibility after being given a sports massage treatment and stretching the upper extremities, and analyzed using the SPSS22 application with the results, of sports massage and stretching of the upper extremities affecting the flexibility with sig Sport Massage exercises upper limb 0.02 and sig value stretching upper limb 0.00. Keywords: Sports Massage of the upper extremities, flexibility